Continued-fractions representations of the functions $sh z, ch z, sin z, cos z$ - Pahirya, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We obtain the representations of the functions $sh z, ch z, sin z,$ and $cos z$ by quasireciprocal functional continued fractionsof the Thiele type.